2010
DOI: 10.1105/tpc.109.072280
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Studies Illuminate the Structural-Functional Model of Plant Phytochromes

Abstract: A synthesis of insights from functional and evolutionary studies reveals how the phytochrome photoreceptor system has evolved to impart both stability and flexibility. Phytochromes in seed plants diverged into three major forms, phyA, phyB, and phyC, very early in the history of seed plants. Two additional forms, phyE and phyD, are restricted to flowering plants and Brassicaceae, respectively. While phyC, D, and E are absent from at least some taxa, phyA and phyB are present in all sampled seed plants and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
95
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 148 publications
(205 reference statements)
4
95
0
2
Order By: Relevance
“…Phytochromes are encoded by three genes (PHYA, PHYB, and PHYC) in most monocot species whereas eudicot plant species possess additional genes (PHYD-F) derived from PHYB duplications (7,8). Studies in model plant species have shown that PHYA is required for growth in deep shade and for seedling deetiolation (9) whereas members of the PHYB clade play major roles in shade-avoidance responses (10,11).…”
mentioning
confidence: 99%
“…Phytochromes are encoded by three genes (PHYA, PHYB, and PHYC) in most monocot species whereas eudicot plant species possess additional genes (PHYD-F) derived from PHYB duplications (7,8). Studies in model plant species have shown that PHYA is required for growth in deep shade and for seedling deetiolation (9) whereas members of the PHYB clade play major roles in shade-avoidance responses (10,11).…”
mentioning
confidence: 99%
“…Examples include a long N-terminal extension (NTE) in plant Phys and pervasive sequence variations within the PAS, GAF, and PHY domains and the downstream OPM (3,4). For a more authoritative view, we present the crystal structure of a Phy PSM from a seed plant, that of PhyB from Arabidopsis thaliana, and extensively characterize its solution and photochemical properties.…”
mentioning
confidence: 99%
“…This information then regulates nearly all aspects of plant growth and development from seed germination to senescence. Notably, seed plants typically express three Phy isoforms (PhyA, PhyB, and PhyC) that control distinct and overlapping photoresponses, with PhyB having a dominant role in green tissues (2,3).…”
mentioning
confidence: 99%
“…Certain groups of plants, such as diploid grasses, have only one copy of PHYA, PHYB, and PHYC, although lineage-specific duplications and losses of phytochrome genes have occurred in many groups of flowering plants (Mathews 2010). Phytochrome mutants in the model plant systems Arabidopsis (Arabidopsis thaliana, Brassicaceae) and rice (Oryza sativa, Poaceae) have contributed to the elucidation of the functional roles of the various phytochromes.…”
mentioning
confidence: 99%
“…Flowering plants typically contain three types of phytochromes referred to as PHYTOCHROME A (PHYA), PHY-TOCHROME B (PHYB), and PHYTOCHROME C (PHYC) (Mathews 2010). Certain groups of plants, such as diploid grasses, have only one copy of PHYA, PHYB, and PHYC, although lineage-specific duplications and losses of phytochrome genes have occurred in many groups of flowering plants (Mathews 2010).…”
mentioning
confidence: 99%